A Comparison Investigation on Antioxidant Activities, Physicochemical Properties and Phytochemical Contents of Kiwifruit Genotypes and Cultivars. Issue 2 (3rd April 2019) - Ozen, Tevfik; Zenginbal, Hamdi; Yazicioglu, Emine; Gul, Fatih; Demirtas, Ibrahim
ABSTRACT: The present work was conducted to find the physicochemical properties, chemical components and antioxidant capacity of kiwifruit hydroalcoholic extracts (B-31, HO-1-14, J-242, Bruno, Greenlight, Hayward, Monty, Topstar) grown Yalova, Turkey. Phytochemical tests were performed to determine total phenolic, flavonoid and ascorbic acid. Moreover, the kiwifruit extracts were subjected to evaluate their antioxidant potential using different in vitro assays such as total antioxidant, inhibition of lipid peroxidation, reducing power, metal chelating, free radical, H2 O2 and superoxide anion scavenging activities at 50–500 μg mL −1, and also found EC50 and IC50 values. The soluble solid content (SSC), titratable acidity (TA) and pH were analyzed in all the genotypes and cultivars. The highest total phenolic, flavonoid and ascorbic acid content were found in J-242 (89.53 mg GAE/100 g), J-242 (109.13 mg QE/100 g) and HO-1-14 (64.15 mg/100 g), respectively. The linoleic, palmitic, stearic and oleic acid methyl esters were detected in all kiwifruit extracts by GC/MS. Significant differences were found between genotypes and cultivars in the antioxidant tests. The extracts showed high inhibition of lipid peroxidation and compared to standards, significantly ( p  < 0.05). The GC/MS analyses confirmed quantitative variability in the antioxidant profiles. The SSC, TA and pH of kiwifruit genotypes and cultivars showed a moderate level. The key parameters for the most active kiwifruit included the following: total antioxidant activity for B-31, H2 O2 scavenging activity for J-242 and metal chelating activity for Topstar. In conclusion, this study exhibited the important role played by the genotypes and cultivars background on the chemical content and antioxidant profiles.